Long Distance Interpersonal Communication Between Parents and Children in Supporting Studies in Final Year Communication Science Students at Telkom University - Yuliani Rachma Putri; Elvina Zenobia Arianto (Dinasti Publisher, 2025)
This study aims to analyze how interpersonal communication of long- distance relationships between parents and children supports studies in final year students of communication science at Telkom University. This study is a descriptive qualitative study using a phenomenological approach. The object of this study is the phenomenon of interpersonal communication involving parents and children of Telkom University students. The population in this study were final year students of Communication Science, Faculty of Communication and Business at Telkom University with a total of 20 respondents from outside Bandung City. Data collection was carried out through interview and documentation methods. The results of this study indicate that interpersonal communication between parents and children is carried out via whatsapp and video calls which have helped and maintained the emotional closeness of both of them while away from home. Most final year students feel helped by the communication they do with their parents in various aspects such as openness, empathy, support, positive feelings and similarities. Although there are still some obstacles in various aspects such as the aspect of openness where students tend not to be too open because they feel the need to be independent or do not want to burden their parents; the aspect of empathy where their parents are less able to understand their academic conditions; the aspect of support where there are still those who do not get enough support from their parents due to busy factors; and aspects of similarity where there are still parents who have different views from their children.